Investigational new drug enabling angiotensin oral-delivery studies to attenuate pulmonary hypertension. (March 2020) - Daniell, Henry; Mangu, Venkata; Yakubov, Bakhtiyor; Park, Jiyoung; Habibi, Peyman; Shi, Yao; Gonnella, Patricia A.; Fisher, Amanda; Cook, Todd; Zeng, Lily; Kawut, Steven M.; Lahm, Tim
Abstract: Pulmonary arterial hypertension (PAH) is a deadly and uncurable disease characterized by remodeling of the pulmonary vasculature and increased pulmonary artery pressure. Angiotensin Converting Enzyme 2 (ACE2) and its product, angiotensin-(1–7) [ANG-(1-7)] were expressed in lettuce chloroplasts to facilitate affordable oral drug delivery. Lyophilized lettuce cells were stable up to 28 months at ambient temperature with proper folding, assembly of CTB-ACE2/ANG-(1-7) and functionality. When the antibiotic resistance gene was removed, Ang1-7 expression was stable in subsequent generations in marker-free transplastomic lines. Oral gavage of monocrotaline-induced PAH rats resulted in dose-dependent delivery of ANG-(1–7) and ACE2 in plasma/tissues and PAH development was attenuated with decreases in right ventricular (RV) hypertrophy, RV systolic pressure, total pulmonary resistance and pulmonary artery remodeling. Such attenuation correlated well with alterations in the transcription of Ang-(1–7) receptor MAS and angiotensin II receptor AGTRI as well as IL-1β and TGF-β1. Toxicology studies showed that both male and female rats tolerated ~10-fold ACE2/ANG-(1–7) higher than efficacy dose. Plant cell wall degrading enzymes enhanced plasma levels of orally delivered protein drug bioencapsulated within plant cells. Efficient attenuation of PAH with no toxicity augurs well for clinical advancement of the first oral protein therapy to prevent/treat underlying pathology for this disease. Graphical abstract: Image 1